Hydro-mechanical influence of sub-seismic blind faults on integrity of CO2 geological storage in deep saline aquifer. (August 2016) - Le Gallo, Yann
Highlights: Quantification of CO2 migration and induced ground level heave and stress changes along a subseismic fault from a large-scale storage project (average injection rate 0.8 Mtpa). Detail mechanical and flow modeling of the fault zone structure (damage zones and fault core). Coupled geomechanical-flow modeling with explicit fault zone gird blocks. Alternate cases highlighting the impact of damage zone hydraulic parameter on CO2 migration along the sub-seismic blind fault. Limited effective stress changes and negligible ground deformation (<1 cm over the 30-year injection) due to CO2 injection. Abstract: Fluid injection in deep sedimentary porous formations might induce shear reactivation of reservoir faults. In this paper, we focus on 'blind' 1000-m-long normal faults (with limited shear displacement c.a. 1 m), which can hardly be detected using conventional seismic surveys, but might potentially enable leakage pathways. In this study, a blind sub-seismic fault was assumed in the vicinity of a CO2 injection well (c.a. 1 km). The study area is in the eastern part of the Paris Basin and targeting the Lower Triassic Sandstone formation which is deemed adequate for CO2 injection. The arbitrary geometry of the fault (with limited throw c.a. 1 m), was set across the expected migration pathway of the injected CO2 . The fault is assumed to extend vertically between the storage and control aquifer. A modeling approach coupling fluid flow and geomechanics is used to assess the pressure impact of the CO2 injection on in-situ fluids and formations. The model extends vertically from the Permian base to the ground surface assuming all layers to be homogeneous except in the storage aquifer where the heterogeneities of the braided channel environment are accounted for. The fault zone is modeled with heterogeneities both in the fault core and damage zones and the control aquifer and is explicitly gridded in the numerical model. In this study the fault core heterogeneities are assumed to be correlated to the Shale Gouge Ratio of the fault. The simulation scenarios aimed for a continuous CO2 injection at a rate of 0.8 Mtpa during 30 years. When assuming the fault does not modify the formation flow and mechanical parameters, very little upward migration of CO2 is computed outside of the storage aquifer. This is not the case when the fault modifies the formation flow and mechanical parameters. In the latter case, the CO2 migrates up to the control aquifer preferably through the fault damage zones rather than through the fault core due to the parameter selection. In both cases, the pressure increase due to CO2 injection in the storage aquifer is small which imply small changes in effective stresses and negligible induced ground deformations. Most of the stress changes are limited to the vicinity of the fault and injection well.